Bioorthogonal SERS Nanoprobes for Mulitplex Spectroscopic Detection, Tumor Cell Targeting, and Tissue Imaging. Issue 37 (23rd July 2015) - Wu, Junzhou; Liang, Duanwei; Jin, Qingqing; Liu, Jie; Zheng, Meiling; Duan, Xuanming; Tang, Xinjing
Abstract A surface‐enhanced Raman scattering (SERS) technique shows extraordinary features for a range of biological and biomedical applications. Herein, a series of novel bioorthogonal SERS nanoprobes were constructed with Gold nanoflower (AuNF) and Raman reporters, the signals of which were located in a Raman‐silent region of biological samples. AS1411 aptamer was also co‐conjugated with AuNF through a self‐assembled monolayer coverage strategy. Multiplex SERS imaging using these nanoprobes with three different bioorthogonal small‐molecule Raman reporters is successfully achieved with high multiplexing capacity in a biologically Raman‐silent region. These Raman nanoprobes co‐conjugated with AS1411 showed high affinity for tumor cells with overexpressed nucleolin and can be used for selective tumor cell screening and tissue imaging.